Peran Kepala Sekolah Dalam Pemanfaatan Teknologi Untuk Meningkatkan Kualitas Pendidikan - Alwi, M. Haddad; Salsabila, Mutiara; Ummah, Nidaul; Purba, Siti Aisyah Br; Nasution, Inom (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In this digital and Industry 4.0 era, information and communication technology plays an important role in the world of education. The integration of technology in the learning process has been proven to improve the quality of education. School principals have a central role in facilitating and encouraging the effective use of technology in schools. As leaders, school principals are responsible for providing adequate technology infrastructure, developing policies and strategies that support the use of technology in learning, and ensuring teachers and students have the necessary skills. This research aims to explore in depth the role of school principals in using technology to improve the quality of education. The research results show that school principals must be leaders in the application of technology, utilizing it as a primary tool to transform the teaching and learning process. The criteria for a school principal as a leader in the use of technology include interpersonal and communication skills, vision, planning and management, technology and infrastructure support, staff development and training, as well as evaluation and research. Effective school principal leadership by optimally utilizing technology can improve the quality of education in schools.